1985
DOI: 10.1161/01.hyp.7.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Selective antagonism of humoral versus neural vasoconstrictor responses by nisoldipine.

Abstract: SUMMARY The effects of nisoldipine administration on vascular reactivity to humoral and neural vasoconstrictor stimuli were examined in the intact rat. For these experiments, rats were instrumented with miniaturized pulsed Doppler flow probes to allow continuous measurement of renal, mesenteric, and hindquarters blood flow. In conscious and anesthetized rats, intravenous doses of angiotensin II (75 and 150 ng/kg), norepinephrine (0.6 and 1.2 /xg/kg), and epinephrine (0.6 and 1.2 /zg/kg) caused dose-dependent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…2). It has been previously shown that calcium antago nists abolish the vasoconstrictor responses to histamine and to a variety of vasoactive agents such as serotonin and catecholamines [1,25,26]. Our findings are in agreement with those of Perez et al [10], who found that in open chest dogs, intravenous infusion of nisoldipine abolished the vasoconstriction of large coronary arteries induced by topical application of potassium ion; Drexler et al [9] also reported that intravenous infusion of nisoldipine in rats induced a significant va sodilatation of coronary arteries during rest and exercise.…”
Section: Discussionmentioning
confidence: 99%
“…2). It has been previously shown that calcium antago nists abolish the vasoconstrictor responses to histamine and to a variety of vasoactive agents such as serotonin and catecholamines [1,25,26]. Our findings are in agreement with those of Perez et al [10], who found that in open chest dogs, intravenous infusion of nisoldipine abolished the vasoconstriction of large coronary arteries induced by topical application of potassium ion; Drexler et al [9] also reported that intravenous infusion of nisoldipine in rats induced a significant va sodilatation of coronary arteries during rest and exercise.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown, however, that Ca 2+ channel blockers attenuate the pressor and regional vasoconstrictor actions of Ang II and norepinephrine. 22 A bolus injection of nicardipine 0.1 mg/kg lowered the blood pressure (see Figure 3, legend) and also partly suppressed the pressor actions of Ang II and norepinephrine (data not shown). However, the result that the rapid pressor response to ET is relatively resistant to nicardipine favors the possibility that the inhibition of the slow pressor response to ET is due to a specific suppressing action of nicardipine.…”
Section: Figure 6 Line Graphs Of Dose-response Relations To Endothelmentioning
confidence: 92%
“…No attempt was made to Identify the aadrenoreceptor subtype involved in the vasoconstrictor actions of noradrenaline and adrenaline. However, these results demonstrate that an influx of extracellular Ca2+ was necessary for the vasoconstrictor actions of these compounds (Lappe et al, 1985). A recent study in humans has also shown that pressor responses to aI-(phenylephrine) as well as (~2 -(amethylnoradrenalhe)-adrenoreceptor s h ulation were inhibited after four days of oral treatment with calcium antagonists (Pasanisi, Elliott, Meredith, Sumner 81 Reid, 1985).…”
Section: C) Discussion Regarding the Effects Of Cakizim Antagonists Omentioning
confidence: 80%